ROLE OF BIOFILM-FORMING BACTERIA IN CHRONIC WOUND INFECTIONS AND THEIR ANTIBIOTIC RESISTANCE PROFILES (Journal of Medical & Health Sciences Review, 2025)
Chronic wound infections are a global health concern, affecting up to 4% of diabetic populations. Biofilm-producing bacteria significantly delay healing and increase multidrug resistance (MDR. This study assessed the prevalence of biofilm-forming bacteria in chronic wounds and their antibiotic resistance patterns. A total of 100 chronic wound samples were collected. Bacterial identification and biofilm quantification were performed using standard microbiological techniques, while antibiotic susceptibility testing followed CLSI guidelines. Data were analyzed using SPSS v26, with p < 0.05 considered significant. Of 100 samples, 85 (85%) showed bacterial growth. Gram-negative isolates predominated (70/85, 82.4%) over Gram-positives (15/85, 17.6%). The most frequent pathogens were Pseudomonas aeruginosa (25, mean 0.29 ± 0.06), Staphylococcus aureus (20, 0.24 ± 0.05), Escherichia coli (15, 0.18 ± 0.04), and Klebsiella pneumoniae (10, 0.12 ± 0.03). Biofilm production was detected in 62 isolates (72.9%): strong (18, 0.29 ± 0.07), moderate (25, 0.40 ± 0.09), and weak (19, 0.31 ± 0.08). Strong biofilm formation was most common in P. aeruginosa (48%, 0.83 ± 0.08) and S. aureus (20%, 0.50 ± 0.08). Antibiotic resistance was high: S. aureus showed 80% penicillin and 60% erythromycin resistance, with 35% MRSA. E. coli (40%) and K. pneumoniae (50%) were ESBL producers. Overall, 45/85 isolates (52.9%, mean 0.53 ± 0.15) were MDR, significantly higher in biofilm producers (67.7%, mean 0.68 ± 0.10) than non-producers (13%, 0.13 ± 0.05; p < 0.01). Polymicrobial infections showed greater biofilm prevalence (83.3%) and MDR (70%) than monomicrobial (45.5%). Chronic wound infections are dominated by biofilm-forming MDR bacteria, particularly P. aeruginosa and S. aureus. Biofilm formation correlates strongly with MDR, wound duration, and polymicrobial infections, emphasizing the need for anti-biofilm therapies in wound management.